Teachers’ experiences of continuous professional development for citizenship and social cohesion in South Africa and Zimbabwe: enhancing capacity for deliberative democracies - Singh, Marcina; Mukeredzi, Tabitha (Frontiers in Education, 2024)
While questions continue to be asked about teachers' content and pedagogical content knowledge to ensure quality education systems, less consideration has been placed on teachers' ability to teach for citizenship and social cohesion that contributes equally to quality education systems. This paper illuminates the understandings of citizenship and social cohesion held by South African and Zimbabwean teachers, their experiences of Continuous Professional Development (CPD) that promote the values of citizenship and social cohesion, and how they practice these learnings in their school contexts. The South African study presents the views of eleven high school teachers where data was procured through semi structured interviews. The Zimbabwean study presents the views of seventeen high school teachers, where data wasprocured through an open-ended questionnaire. The two studies suggest that teachers in South Africa and Zimbabwe share similar perspectives on citizenship and social cohesion, emphasizing nation-building and respect as key drivers. Teachers also report aligning their teaching practices with citizenship and social cohesion values with a limited focus on political participation, possibly due to fear of negative repercussions. Further, CPD for citizenship and social cohesion is fragmented, inconsistent and mostly absent. This study is an important contribution to debates about improving quality education and ensuring deliberative democracies in post-conflict and postcolonial states in the Global South. Teachers play a critical role in socializing schoolchildren for citizenship. As such, they need to be equipped with the skills that allow them to do so. Further to this, teachers also need the freedom and autonomy to discuss politics in the classroom without fear of negative repercussions, including alienation and fear of losing their jobs.